Nutritional Modelling for Pigs and Poultry 2014
DOI: 10.1079/9781780644110.0259
|View full text |Cite
|
Sign up to set email alerts
|

Response of laying hens to amino acid intake.

Abstract: This study was designed to measure the responses of Dekalb laying hens to three amino acids such that the optimum economic amino acid intakes of these hens could be determined, taking into account variation in body weight and potential egg output in the population as well as changes in egg revenue and feed price. Three experiments were conducted with Dekalb White laying hens during the period from 33 to 48 weeks of age, with each trial being divided into four periods of 28 days. Responses were measured to inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…During the experimental periods (Assay 1 and 2), it was observed that the hens presented lower feed intake in relation to indicated by the Hy‐line W36 guideline, probably, due to the severity in the protein and amino acids reduction. This is a common characteristic of this type of study due to the formulation technique used to formulate experimental diets (Bendezu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During the experimental periods (Assay 1 and 2), it was observed that the hens presented lower feed intake in relation to indicated by the Hy‐line W36 guideline, probably, due to the severity in the protein and amino acids reduction. This is a common characteristic of this type of study due to the formulation technique used to formulate experimental diets (Bendezu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As the deficiency in the diets become more severe, the feed intake is depressed because of the increase in the heat production (Bowmaker and Gous, 1991;Bendezu et al, 2015), in part, resulting from the deamination process of other AA that are in excess and are not being used for protein synthesis (Cadirci et al, 2009). This is a common characteristic of this type of study due to the formulation technique used for the experimental diets (Bendezu et al, 2015). In adult hens, an AA deficiency results in net catabolism of body proteins to supply the AA to prevent a distortion in the plasma and tissue AA levels (Cadirci and Smith, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…During the experimental periods, it was observed that the hens did not consume the amount of the feed allotted (Tables and ), probably, because of the severity in the AA reductions. As the deficiency in the diets become more severe, the feed intake is depressed because of the increase in the heat production (Bowmaker and Gous, ; Bendezu et al., ), in part, resulting from the deamination process of other AA that are in excess and are not being used for protein synthesis (Cadirci et al., ). This is a common characteristic of this type of study due to the formulation technique used for the experimental diets (Bendezu et al., ).…”
Section: Discussionmentioning
confidence: 99%